Penerapan Algoritma Machine Learning Random Forest untuk Prediksi Risiko Konversi Sindrom Terisolasi Klinis Menjadi Multiple Sclerosis - Ripaldi, Riki; Tambunan, Leonardo Sebastian; Edowardo, Samuel; Rahkmah, Syifa Nur; Sutoyo, Imam; Sariasih, Findi Ayu (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
Clinically Isolated Syndrome (CIS) is an initial neurological episode potentially developing into Multiple Sclerosis (MS), a chronic neurodegenerative disorder of the central nervous system. Early detection of risk factors for CIS to MS conversion is crucial for supporting timely medical interventions and slowing down disease progression. This study aims to develop a risk prediction model for CIS to MS conversion using a Machine Learning algorithm, comprehensively evaluate the model's performance, and implement it as a web-based clinical decision support system. The research employs a machine learning approach utilizing the Random Forest Classifier to predict the conversion risk using the public dataset Conversion Predictors of CIS to Multiple Sclerosis. The dataset comprises 273 patients with clinical variables including demographics, initial symptom characteristics, Magnetic Resonance Imaging (MRI) findings across various brain regions and the spinal cord, and Oligoclonal Bands (OCB) test results. The methodology involved addressing class imbalance using weight adjustments, cross-validation, and implementing a custom threshold of 0.57 to minimize false positives, ensuring clinical diagnostic safety. Test results demonstrate that the Random Forest model achieved optimal performance with an Accuracy of 81.82%, an F1-Score of 0.82, and an Area Under the Curve (AUC) of 0.9140, indicating excellent discriminative capability. Feature Importance analysis revealed that Oligoclonal Bands (OCB), Initial Symptoms (specifically sensory and visual disturbances), and MRI lesions (especially Periventricular) are the most influential predictors. The model is subsequently implemented into a web-based prediction system to facilitate interactive risk assessment by medical professionals. This implementation serves as an accurate and explainable prototype of a Clinical Decision Support System.